Observation of kerr rotation in spin-coated yttrium iron garnet (YIG) - polymer composite - Jemei Ng. (2002., 2002)
In this project, preparation of thick film that containing elements to form Yttrium Iron Garnet (YIG) by sol-gel technique using spin coating machine was carried out. This is because by sol-gel technique it was hoped to produce thisk film of gel containing elements to form YIG with superior characteristics. This project was carried out in order to obtain YIG phase at temperature lower than those obtained by the conventional ceramic method. The samples were produced by preparing a solution, which had been stirred at room temperature using a magnetic strrer until a formation of gel occurred. The gel was then heat at 80 degreeC. to vaporize the unneeded water molecule. The thick gel was then made to undergo heat treatment in the furnace and later mixed with PVA to form YIG polymer composite. Later on, the mixture was squirted onto the spin-coated machine to produce thick film. X-ray Diffraction (XRD) was done to investigate the garnet phase. Surface magneto-optic Kerr Effect measurements were then performed on the YIG thick film polymer composite, which was subjected to an applied field and room temperature. The Kerr effect to be observed was in the thick film containing elements in the ratio for YIG formation Finally we determined that the Kerr rotation was less than 3 degree which is what we expect to get. We can conclude that the objectives of this project were successfully achieved.
Project paper (B.S.(Hons)) - Universiti Putra Malaysia, 2002.